In vitro Impact of Yeast Expressed Hybrid Peptide CATH-2TP5 as a Prophylactic Measure Toward Sepsis and Inflammation - Ahmad, Baseer; Hanif, Quratulain; Wei, Xubiao; Zhang, Lulu; Sabir, Naveed; Li, Zhongxuan; Cheng, Junhao; Khan, Shahzad Akbar; Basit, Abdul; Shahid, Muhammad; Rehman, Amin ur; Si, Dayong; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
CATH-2TP5 is a linear cationic hybrid peptide, consequent from naturally occurring antimicrobial peptide (AMPs) Cathelicidin-2 (CATH-2) and Immunomodulatory peptide Thymopentin (TP5), having dynamic and potent anti-inflammatory potential without hemolytic activity. The biocompatible mechanism of CATH-2TP5 essentials to explore new methodologies in the direction of biomedical applications. In this retrospectively study, an antiendotoxin and anti-inflammatory hybrid peptide CATH-2TP5 was emulated into pPICZα-A and successfully expressed in Pichia pastoris (P. pastoris). The recombinant CATH-2TP5 was purified through the Ni-affinity column and Reversed-phase HPLC. The purified CATH-2TP5 peptide exhibited robust anti-endotoxin activity and significantly (p < 0.05) neutralized the effect of lipopolysaccharide (LPS). Furthermore, CATH-2TP reduced the LPS-induced cytotoxic effects in murine RAW264.7 macrophages and significantly (p < 0.05) diminished the nitric oxide secretion and pro-inflammatory cytokines including TNF-α, IL-6, IL-1β, as well. In addition, associated to control and parental peptide the number of apoptotic cells was contracted with the treatment of CATH-2TP5. Collectively, this study provides a platform to comprehend the molecular mechanism of the expression and improvement of CATH-2TP5 peptide which may act as a therapeutic drug at the mass level.